2022
DOI: 10.53730/ijhs.v6ns4.12131
|View full text |Cite
|
Sign up to set email alerts
|

study of the potential of by-products from pineapple processing in Thailand

Abstract: The data, focusing on the supply of pineapple for industrial processing in Thailand during the period from 2011-2020, was acquired. The data indicated that productivity had tended to decrease during the period between 2011-2015 due to phenomena of drought and a reduction in prices, while increasing trends were observed during the years between 2016 - 2019. In the year 2020, Thailand was the biggest exporter of canned pineapple in the world, and the export value was approximately 345 million U.S. dollars. Durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…In our study, the amounts of pineapple by-products obtained after fruit processing nearly double those (skin, shoot tip, core, stems, crowns) reported by other investigations [8,14], except for the peel. In terms of chemical composition, in other studies on pineapple by-products [8,13,14,19,23], it is reported that CP, EE, NDF, and ADL range from 4.4-5.7, 0.2-1.2, 20.5-44.69, and 23.04-39.40% DM, respectively. The same references also quantified organic matter (OM), non-fiber carbohydrate (NSC), and water-soluble carbohydrate (WSC), resulting, respectively, in 95.54, 48.8, and 5.4% DM.…”
Section: Chemical Characteristics and Estimated Me Energy: Comparing ...supporting
confidence: 69%
See 1 more Smart Citation
“…In our study, the amounts of pineapple by-products obtained after fruit processing nearly double those (skin, shoot tip, core, stems, crowns) reported by other investigations [8,14], except for the peel. In terms of chemical composition, in other studies on pineapple by-products [8,13,14,19,23], it is reported that CP, EE, NDF, and ADL range from 4.4-5.7, 0.2-1.2, 20.5-44.69, and 23.04-39.40% DM, respectively. The same references also quantified organic matter (OM), non-fiber carbohydrate (NSC), and water-soluble carbohydrate (WSC), resulting, respectively, in 95.54, 48.8, and 5.4% DM.…”
Section: Chemical Characteristics and Estimated Me Energy: Comparing ...supporting
confidence: 69%
“…These products are known to be rich in many nutrients, such as vitamins (i.e., A, C, B 1 , B 6 , folic acid, betacarotene), minerals (i.e., copper, manganese), and other compounds with antioxidant, digestive (bromelain), anti-inflammatory, and analgesic properties [5,6]. During fruit processing, a large quantity (about 65%) of leftovers is discarded as waste, including the peel (35.5%), core (14.7%), pomace (6.0%), bud end (4.6%), and crown (4.3%) [7,8]. Concerning the amount of fruit produced worldwide, more than 18 million tons of pineapple leftovers are generated annually.…”
Section: Introductionmentioning
confidence: 99%
“…Thailand is currently the second-largest supplier of processed pineapple fruit in the world. Production areas for pineapple in Thailand have been divided into northern, northeastern, central, and southern parts [ 12 ]. Most cultivated areas are in Prachuap Khiri Khan, Rayong, Ratchaburi, and Chonburi provinces [ 11 ].…”
Section: Introductionmentioning
confidence: 99%